A phylogenetic analysis of the megadiverse Chalcidoidea (Hymenoptera). (4th January 2013) - Heraty, John M.; Burks, Roger A.; Cruaud, Astrid; Gibson, Gary A. P.; Liljeblad, Johan; Munro, James; Rasplus, Jean‐Yves; Delvare, Gerard; Janšta, Peter; Gumovsky, Alex; Huber, John; Woolley, James B.; et al.
Abstract: Chalcidoidea (Hymenoptera) is extremely diverse with an estimated 500 000 species. We present the first phylogenetic analysis of the superfamily based on both morphological and molecular data. A web‐based, systematics workbench mx was used to score 945 character states illustrated by 648 figures for 233 morphological characters for a total of 66 645 observations for 300 taxa. The matrix covers 22 chalcidoid families recognized herein and includes 268 genera within 78 of 83 subfamilies. Morphological data were analysed alone and in combination with molecular data from ribosomal 18S (2105 bp) and 28S D2–D5 expansion regions (1812 bp). Analyses were analysed alone and in combined datasets using implied‐weights parsimony and likelihood. Proposed changes in higher classification resulting from the analyses include: (i) recognition of Eriaporidae, revised status ; (ii) recognition of Cynipencyrtidae, revised status ; (iii) recognition of Azotidae, revised status ; (iv) inclusion of Sycophaginae in Agaonidae, revised status ; (v) reclassification of Aphelinidae to include Aphelininae, Calesinae, Coccophaginae, Eretmocerinae and Eriaphytinae; (vi) inclusion of Cratominae and Panstenoninae within Pteromalinae (Pteromalidae), new synonymy ; (vii) inclusion of Epichrysomallinae in Pteromalidae, revised status . At a higher level, Chalcidoidea was monophyletic, with Mymaridae the sister group of Rotoitidae plus the remaining Chalcidoidea. A eulophid lineage was recovered that included Aphelinidae, Azotidae, Eulophidae, Signiphoridae, Tetracampidae and Trichogrammatidae. Eucharitidae and Perilampidae were monophyletic if Eutrichosomatinae (Pteromalidae) was included, and Eupelmidae was monophyletic if Oodera (Pteromalidae: Cleonyminae) was included. Likelihood recovered a clade of Eupelmidae + (Tanaostigmatidae + ( Cynipencyrtus  + Encyrtidae). Support for other lineages and their impact on the classification of Chalcidoidea is discussed. Several life‐history traits are mapped onto the new phylogeny.